EFEKTIVITAS MODEL PIMCA DENGAN MULTI-REPRESENTASI PADA PEMBELAJARAN GERAK LURUS BERUBAH BERATURAN (GLBB) KELAS X IPA DI SMA KATOLIK THOMAS AQUINO MANADO - Christo Palit; Cosmas Poluakan; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
This study aims to determine the increase in student learning outcomes in physics subjects by the PIMCA (Presentation, Idea Mapping, Conceptualizations, Formative Assessment) model with multi-representation in Uniformly Changing Straight Motion (GLBB). The type of research carried out was quantitative with the Pre-Experiment Design method because there was only one treatment group that was chosen to determine the achievement of learning outcomes and the research design used was the one grub pretest-posttest design. The instrument used is the Pre-test to test the students' initial abilities, then they are given treatment, namely PIMCA and finally the Post-test is given to find out the results after the treatment is applied. The research is located at Thomas Aquino Catholic High School Manado. The sample tested was class X IPA 1 academic year in the odd semester 2020/2021 with a total of 20 students as respondents. The results of data processing and analysis obtained the average value of the Pre-test 28 and the average value of the Post-test 71 and carried out statistical testing with the paired sample test t-test obtained a sig. (2-tailed) value of 0.000 <0.05 so there is an increase in student physics learning outcomes after the treatment is applied.